Advanced mechanical properties obtained via transition metals doped in CrFeNi medium entropy alloy - Md. Nadim Mahamud Nobin; Zahid Hasan; Md. Zahidur Rahaman; Md. Lokman Ali (Journal of Materials Research and Technology, 2024)
Medium entropy alloys (MEAs) have attracted significant interest due to their exceptional mechanical characteristics. This study employs molecular dynamics simulations to investigate the impact of transition metal (TM) elements doping on the mechanical properties of face-centered cubic (FCC) (CrFeNi)100−xTMx(TM=Cu,Mo,Nb,Tiandx=0,4) MEAs. We have doped 4% TM elements with pure CrFeNi MEA and analyze several mechanical characteristics such as lattice distortion, Yield strength, elastic constants and moduli, Vickers hardness, machinability index, and Kleinman parameters. The correlation between elastic moduli and doping implies a decrement in the stiffness of (CrFeNi)100−xTMx alloys. To confirm the ductility, a thorough assessment involving Poisson's ratio, Cauchy's pressure, and Pugh's ratio are conducted. According to the anisotropy factor analysis, the presence of doping increases anisotropy in (CrFeNi)100−xTMx MEAs. The findings of our work suggest that the improved mechanical properties can be beneficial in the development of MEAs suitable for diverse applications.